2009
DOI: 10.1111/j.1365-2788.2009.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Hope as a psychological resilience factor in mothers and fathers of children with intellectual disabilities

Abstract: Hope is a construct that merits further investigation within families research, and is potentially a factor that could be utilised in intervention to help increase familial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 40 publications
9
106
0
8
Order By: Relevance
“…Hope and mindfulness have been explored to be effective to optimise psychological resilience. 14,15 However, there could still be different psychological processes underlie resilience across the lifespan after health problems. 16 Future intervention research targeting patients with chronic illnesses would be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Hope and mindfulness have been explored to be effective to optimise psychological resilience. 14,15 However, there could still be different psychological processes underlie resilience across the lifespan after health problems. 16 Future intervention research targeting patients with chronic illnesses would be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The answers to every statement were on a 5-point Likert-type scale ranging from never (1) to always (5), respectively. The validity of this questionnaire and its components were measured by its designers through internal consistency and test-retest methods with acceptable values (Lloyd & Hastings, 2009). Discriminant validity and construct validity of this questionnaire have also been reported at a desirable level.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…It was originally developed to screen and identify children with learning diff iculties. In this inventory; learning diff iculties have been categorized into f ive components related to the reading, accounting, social cognition, social anxiety, and spatial functions with good psychometric characteristics (Lloyd & Hastings, 2009). The complete dataset required for this study were collected through this questionnaire.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their hopes in certain help them to be more positive in surrounding and becoming an optimist personality in providing care to their children with SpLD. In fact, it was found that having hope could be a resilience factor for the psychological wellbeing of caregiver of children with disability (Lloyd & Hastings, 2009). With hope, they may feel more positive to overcome all challenges and negative feelings in their experience in taking care children with disabilities.…”
Section: Introductionmentioning
confidence: 99%